Evaluación de la recuperación del suelo utilizando tres abonos orgánicos a diferentes dosis en el cultivo de la zanahoria (daucus carota) sector Salache, Cantón Latacunga, Provincia Cotopaxi 2019 – 2020. - Rojano Escobar, Migue Ángel (2020)
This research was carried out at the Salache Experimental Center, Canton Latacunga, Cotopaxi province, at coordinates 78 ° 37'26.9 "W, 01 ° 00'01.0" S at 2800 meters above sea level on the bank terraces. It has an alkaline soil with a pH of 10.40 in which the soil recovery was evaluated using three organic fertilizers at different doses in the carrot crop (Daucus carota) Salache sector, Latacunga canton, and Cotopaxi province 2019 - 2020.The randomized complete block design (DBCA) was applied, with 10 treatments and three repetitions, giving a total of 30 experimental units, the trial was established in an area with the following dimensions of 4 meters wide by 2.5 long giving a result of ten square meters for each experimental unit.The results of the investigation revealed that applying organic fertilizers such as (eco fertilizer, vermicompost, guinea pig fertilizer) at different doses; from 20 t / ha, 30 t / ha, 40 t / ha significantly increased the percentage of macronutrient (NPK) in the final soil analysis. Regarding the pH, the fertilizer that was located in the first range of significance is the echo bonaza with a pH of 10.40 at the beginning and at the end the pH of 9.56 followed by vermicomposting of 9.87, fertilizer of which 9 , 89 and the control 10,16. In the variable number of leaves the treatment (T3 aco abonaza 40 to / ha) at 30, 45,60,75,90,105 days is in the first range of statistical significance; in the variable Plant height treatment (T2 echo fertilizes 30 t / ha) at 30,45,60,90,105 days is in the first range of significance. In the variable yield, the best treatment was T2 with a cost benefit of 0.67.Due to the results presented, the best treatment is T3 to recover the eroded soil of Salache, as an alternative to carrot cultivation.